Antibiotic-loaded Sr-doped porous calcium phosphate granules as multifunctional bone grafts. Issue 2 (1st February 2016) - Marques, C.F.; Lemos, A.; Vieira, S.I.; da Cruz e Silva, O.A.B.; Bettencourt, A.; Ferreira, J.M.F.
Abstract: Multifunctional porous calcium phosphate granules intended as osseous fillers and drug carriers were designed. Strontium- and magnesium- co-substituted biphasic hydroxyapatite (HA)/β-tricalcium phosphate powders (TCP) with compositions close to the mineral part of human bone [(Ca+Sr+Mg)/P=1.62] were prepared by precipitation, heat treated and deagglomerated, and characterized by XRD and SEM. Highly concentrated aqueous suspensions (up to 60 vol%) were prepared from the powders heat treated at 1000 °C. Starch was added as pore forming agent and the suspensions were dripped into a setting sodium alginate solution to obtain spherical granules. Drying and sintering enabled obtaining porous granules that were impregnated with an antibiotic solution (levofloxacin), frozen and then lyophilized. The drug release profile was then assessed in vitro by UV spectrophotometry, with the best release profile being obtained for the Sr-doped granules. The granules׳ osteocompatibility was evaluated using a pre-osteoblastic cell line. The Sr-doped granules exhibited the highest proliferation yields and efficiency in osteoblastic maturation, including acquisition of a differentiated morphology and high levels of secreted alkaline phosphatase. The microstructural features and the in vitro performance of the granules make them promising multifunctional materials for applications in tissue engineering as antibiotic-loaded bone grafts.